Berbagi Praktik Baik Penerapan Model Pembelajaran Inovatif di SMP Negeri 18 Pekanbaru - Sri Ulfa Insani; Sity Rahmy Maulidya; Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This community service is in SMP Negeri 18 Pekanbaru. The material provided is to share good practices in implementing innovative learning models. The application of varied learning models can eliminate student boredom and hone students' learning abilities, which has a positive effect on student success. This training is expected to help students think critically, reason, solve problems and make decisions. The impact that this activity is increasing teacher understanding regarding the application of innovative learning models.